Islamic Modes for Agricultural Financing: Which is the Most Suitable? - Napitupulu, Rodame Monitorir; Rusydiana, Aam Slamet; Pratomo, Wahyu Ario (Department of Islamic Economics, IPB University, 2025)
The agricultural sector is a primary sector in a country, contributing to GDP, providing raw materials for industry, and ensuring food and nutritional security. Additionally, the agricultural sector often proves to be a stabilizing force for the national economy during economic crises. One financing model suitable for this sector is the sharia-compliant financing scheme. This study employs a bibliometric analysis to explore the extent of research on Islamic financing models for the agricultural sector, analyzing 41 Scopus-indexed journal articles. Six main themes emerge: conceptualizing Islamic agricultural financing, waqf technology for SDGs in agribusiness, risk management in Islamic agricultural credit, Islamic finance for agricultural projects, economic growth through Islamic agricultural finance, and Islamic Microfinance Institutions (IMFIs) in agricultural finance. The analysis identifies the most suitable Islamic financing modes as integrated salam contracts with IMFIs, Waqf Trustee-Anchor Company models for agribusiness on waqf land and crowdfunding models with salam contracts and muzaraah waqf. Additionally, qard-al-hasan, muzaraah, and aPLS (agricultural Production and Loss Sharing) scheme with ujrah principles are recommended for unproductive land development. Policymakers in the agricultural sector can leverage these findings to enhance the role of Islamic finance in fostering agricultural development, particularly in countries with a majority Muslim population.